Scar-based analysis and eyewitness accounts of entanglement of humpback whales (Megaptera novaeangliae) in fishing gear in Iceland - Basran, Charla Jean, 1988- (2014)
Læst til 25.2.2015 Entanglement in fishing gear, or bycatch, of cetaceans is a global issue causing thousands of injuries and mortalities each year. Humpback whales (Megaptera novaeangliae) are one of many cetacean species that become entangled, often non-lethally, in various types of fishing gear, which has detrimental impacts on the whales and can cause damage to the gear. Scar-based analysis can be used to determine the estimated number of humpback whales in a population that have been previously entangled in fishing gear. For this study, scar-based analysis, as well as a survey of fishermen aimed to collect eye-witness entanglement accounts, were conducted to estimate the percent of the Icelandic North Atlantic humpback whale subpopulation that has been entangled in fishing gear, and to learn about these events taking place in Icelandic waters. To conduct scar-based analysis, photographs of individual humpback whale flukes and caudal peduncles were taken in Skjálfandi Bay, Iceland and were examined for evidence of wrapping scars and notches which are indicative of entanglement. Results of the scar-based analysis determined that a minimum of 41.8% of the Icelandic subpopulation has been previously entangled. The survey aimed at fishermen reported 6 eye-witness entanglement accounts involving humpbacks interacting with a variety of fishing gear including seine nets, hook-and-line gear, and gillnets. Though further research into entanglement issues in Iceland should be conducted to gain a clearer understanding of the impacts on the whales and the fishermen, results from this study suggest that there is significant entanglement of this subpopulation. These results could warrant some mitigation and management strategies. The development of an entanglement reporting system could aid in gathering data to make informed management decisions. This study suggests the introduction of regulations to keep fishing activities at a safe distance from whales. Further investigation into the use of whale-safe fishing gear ...